Banachs space: Lviv and the Scottish Cafe - Henderson, D. (Condensed Matter Physics, 2004)
In a sense Stefan Banach is the patron saint of this workshop. He was one of the most prominent former residents of Lviv. His “hangout”, the Scottish Cafe, is shown in the street scene that is the cover of the book of abstracts.